MARKET ORIENTATION AND HIGHER EDUCATION: OPTIONS IN A CHANGING WORLD - N., Barnabas (Ushus Journal of Business Management, 2003)
This paper concentrates on the changes that are taking place in the higher education sector worldwide and explains how a more market oriented approach would enable the institutions to perform better. The author also suggests measures to make the institutions more market oriented and makes an effort to develop an education marketing mix.